MEMBANGUN MOMENTUM BARU PEMBANGUNAN PEDESAAN DI INDONESIA - Erizal Jamal (Badan Penelitian dan Pengembangan Pertanian, 2009)
Developing new momentum of rural development in IndonesiaMuch has happened in the new order era of the Indonesia rural development, including the achievement of a high level of rural economic growth and the development of physical infrastructure. At the same time, Indonesia still faces enormous rural development problems especially it has been far from equitably distributed opportunity among the people to participate in the rural development process itself. When we made some comparison with South Korea, in rural development with Saemaul Undong movement, there are two problems in Indonesia rural development which it related with the loss of the rural development momentum and lack of rural individual and community development. In the beginning of 1960’s, the Indonesia rural condition was relatively same with South Korea, poor infrastructure and massive poverty in rural area. The South Korea rural development based on the systematic human resources development and invested heavily in improving the infrastructure for agriculture production. The Korea government has to ease regulations related to farmland ownership, only farmers should be allowed to own farmland. Through these programs, the number of farmers in rural areas decline sharply and average household land ownership increase in the last twenty years. To accelerate the process of rural development in Indonesia, the government needs to establish a new momentum to capture and combine the spirit of individualities and active participation of the farmers as a part of rural community.